445 Protein supplementation in late gestation affects maternal skeletal muscle gene expression and plasma circulating amino acids. (7th December 2018) - Gionbelli, M; Lopes, R; Trece, A; Teixeira, P; Duarte, M; Sampaio, C
Abstract: The second half of beef cows gestation in tropical areas usually occurs during the drought season, where pastures are low in CP. The objective was to evaluate the effects of CP supplementation during the last third of gestation on beef cows weight variation and indicators of nutrient uptake and skeletal muscle mobilization. Forty-three pregnant (gestating males) Nellore cows (543 ± 66 kg) were divided into 8 paddocks (5–6 cows per paddock) of Urochloa decumbens pasture. Four paddocks were supplemented daily with 2 g/kg of a 43.5% CP supplement (SUP, n = 4) and four received only a mineral supplement (CON, n = 4). Treatments started 90 days before the predicted calving date. Liver and Longissimus muscle biopsies for relative mRNA expression and circulating plasma levels of AA were taken at 270 days of gestation. Data were analyzed using MIXED procedure of SAS considering dietary treatment as fixed effect. Differences were declared at P < 0.10. Supplemented cows had greater weight at calving ( P = 0.065) and lost less maternal tissues (without considering gestation-related compounds) ( P = 0.052) but the calf birth weight was not affected ( P = 0.649). Control cows had greater circulating levels of total AA, non-essential AA, glucogenic AA, His, Met, Ala Asn and Ser ( P < 0.10) than supplemented cows, probably due to mobilization of skeletal muscle to support liver gluconeogenesis. The expression of mRNA markers for gluconeogenesis in liver was not affected by the supplementation ( P > 0.10). Supplemented cows had greater expression of mRNA markers for protein synthesis in muscle ( P < 0.10) but not for protein degradation ( P > 0.10). In conclusion, CP supplementation for beef cows in late gestation reduces the maternal weight loss probably by giving more substrates for gluconeogenesis and thus reducing the mobilization of AA from maternal skeletal muscle.